Analisis Analysis Of Public Transport Subsidy For Students In Medan City - Awaliyah Matondang, Khairani; Wardana, Vidia; Rezeki Ramadhani, Mentari; Eleonore Nadapdap, Yemima (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The population continues to increase every year, and so do transportation needs. This is inseparable from the increasing number and variety of population activities. also includes educational activities. Traveling to and from school often results in traffic jams. Apart from that, many students choose to use private vehicles. which worsens air pollution and traffic congestion. Thus, the aim of this research is to create regulations governing the use of public transportation, especially for students. can facilitate student transportation to and from school. Thus, perhaps this can be implemented in the future. This is an example of how the government can provide incentives for students to use public transportation in an effort to reduce congestion caused by the use of private vehicles. The data collection process was carried out using observation, interviews, surveys and paperwork methods, then procedures for analyzing student characteristics and analyzing subsidy mechanisms. Based on various analyzes conducted, based on these findings, 69% of students are willing to switch to subsidized public transportation